Implementation of Electronic E-Auction to Improve Shipyard Supply Chain Performance - Intan Baroroh; Dian Trihastuti; Minto Basuki; Bagiyo Suwasono; Tuesdaysaka Gustaf Wasito (International Journal of Marine Engineering Innovation and Research, 2025)
Material procurement in the supply chain accounts for 60% of the ship contract value and has the highest burden with the largest portion of fund distribution, often resulting in procurement delays. This has an impact on delays in the delivery of modular ship construction. Supply chain performance delays are partly due to conventional auction methods, which result in many cases of fraud and a greater potential for material delays. The potential for losses results in delays in ship production, even though risk assessment activities have been carried out as an improvement for the shipyard. The purpose of web-based electronic auction research is to find efficient and accountable prices that can be justified. On the other hand, manual meetings are not necessary, as vendors can participate in meetings and the auction process from their respective locations, minimizing the potential risk of delays in the supply chain material procurement and enabling the production process to proceed according to the initial contract. The results of the research are in the form of an E-Auction user interface for auction processes with two functions, namely administrator login and login for partners or vendors implementing E-Auction auctions, thereby improving aspects of technology, management, marketing, and human resources.